ADAPTATION AND PATHOLOGICAL CHANGES IN CERVICAL INTERMEDIATE DISCS DUE TO SITTING CONDITIONS (Лучшие интеллектуальные исследования, 2024)
Abstract : This is it research long time during sitting down of work neck spine step and intermediate on disks surface coming adaptation processes and pathological to changes effect to learn dedicated . Descriptive and histological analysis results neck on disks degenerative of processes long time during static in case to be with depends that shows . Research results adaptation mechanical systems to understand and prevention get measures according to practical recommendations own into takes